Development of platinum-niobium as a CO tolerant catalyst for PEFC operating with CO contaminated hydrogen - Rocha, Thairo A.; Colmati, Flavio; Ciapina, Eduardo Gonçalves [UNESP]; Linares, José J.; Gonzalez, Ernesto Rafael (The Electrochemical Society, 2015)
This paper presents the results of a bimetallic Pt3Nb/C catalyst prepared by thermal treatment in dilute reductive atmosphere (5% H2 in Ar) to obtain a CO-tolerant catalyst. The thermal treatment leads to the formation of a PtNb fcc solid solution and a Pt3Nb intermetallic phase along with some niobium oxides (NbO2 and NbO1.46). Such crystalline phases modify the electronic environment of platinum, reducing the white line of the Pt L3 absorption edge, as a result of the filling of the Pt 5d band. This, in turn, weakens the Pt-CO adsorption strength, which, in combination with the large availability of oxygenated species coming from the Nb oxides, leads to a very active CO-tolerant anode electrocatalyst, as confirmed by the CO stripping characteristics and the fuel cell performances in the absence and presence of CO in the H2 fuel stream.